Thibault Darcillon, Économie politique de la libéralisation financière. Les réformes de dérégulation financière et de corporate governance dans les pays de l’OCDE - Thibault Darcillon (Revue de la Régulation)
The dissertation proposes a cross-country analysis of financial deregulation reforms and corporate governance reforms in most of the OECD countries from 1970. Whereas standard models in economics tend to focus on efficiency effects this dissertation uses the institutional complementarity hypothesis to emphasize the impact of financial markets on labor market. Using panel data models empirical results thus indicate that financial reforms have strong distributive effects. Financial liberalization and the rise of institutional investors have directly affected the way of firms’ financing. It is argued that due to institutional complementarities the adoption of financial reforms is likely to affect the institutional equilibrium by modifying the balance of power between social groups.